Self-Reported Responses to Player Profile Questions Show Consistency with the Use of Complex Attentional Strategies by Expert Horseshoe Pitchers - Fairbrother, Jeffrey T.; Post, Phillip G.; Whalen, Sam J. (Frontiers in Psychology, 2016)
The advantages on an external focus of attention have been demonstrated for a variety of sport tasks. The constrained action hypothesis (Wulf, McNevin, & Shea, 2001) argues that focusing externally on the movement effect results in the use of automated processes for movement control. In contrast, focusing internally in an attempt to control the movements of the body disrupts normally automated processes and degrades performance. Research on experts, however, suggests that they may adopt more complex attentional strategies. The present study provided a unique opportunity to examine expert horseshoe players’ attentional strategies as indicated by their self-reported responses to questions included in a National Horseshoe Pitchers Association (NHPA) player profile questionnaire. Responses submitted by 83 top NHPA players were examined to determine the frequency of references to the use of internal and external focus points and identify categories related to attentional strategies. Results indicated that the large majority of players reported using focus points that are consistent with an external focus of attention and that their thoughts corresponded to one or more categories related to technique, mental focus or concentration, general success, use of external focus cues, and emotional control. The findings are consistent with the view that experts may adopt complex attentional strategies that encompass both an external focus and thoughts about a variety of other performance related factors